Early post-surgical cognitive dysfunction is a risk factor for mortality among hip fracture hospitalized older persons. Issue 2 (February 2017) - Ruggiero, C.; Bonamassa, L.; Pelini, L.; Prioletta, I.; Cianferotti, L.; Metozzi, A.; Benvenuti, E.; Brandi, G.; Guazzini, A.; Santoro, G.; Mecocci, P.; Black, D.; et al.
Abstract Summary This study investigates the relationship between cognitive dysfunction or delirium detected in the early post-surgical phase and the 1-year mortality among 514 hip fracture hospitalized older persons. Patients with early cognitive dysfunction or delirium experienced a 2-fold increased mortality risk. Early post-operative cognitive dysfunction and delirium are negative prognostic factors for mortality. Background and purpose Premorbid cognitive impairment and dementia in older individuals negatively affect functional recovery after hip fracture. Additionally, post-operative delirium is an established risk factor for negative outcomes among hip fracture patients. While the majority of hip fracture patients experience minor post-surgical cognitive dysfunction, the prognostic value of this phenomenon is unknown. Therefore, we investigated the relationship between minor cognitive dysfunction or delirium detected in the early post-surgical phase and the 1-year mortality after index hip fracture. Subjects and methods We enrolled 514 patients with hip fracture (77.4 % women), aged 65 years or older (mean age 83.1 ± 7.3 years), who underwent surgical hip fracture repair. Patients were assessed daily from the second to the fourth post-operative day and at 3, 6, and 12 months thereafter. All participants underwent comprehensive assessment, including detection of delirium by using the confusion assessment method and evaluation of cognitive function by using mini-mental state examination (MMSE; score range 0 to 30, with lower scores indicating poorer performance). In the absence of delirium, post-surgical cognitive dysfunction was defined as having low performance on MMSE. Vital status of 1 year after the index fracture and date of death were gathered from local registries. Results The observed 1-year mortality rate was 14.8 %. Men were more likely to die than women within 1 year of the index fracture (p < 0.01). Compared to participants with better cognitive performance, those with MMSE < 24, as well as those with delirium in the post-operative phase, showed a significantly higher 1-year mortality rate (23.3 versus 17.9 and 8.1 %, respectively). Independent of age and sex, post-operative cognitive dysfunction as well as delirium was both associated with a 2-fold increased mortality risk. Conclusions The presence of minor cognitive dysfunction in the early post-surgical phase is a negative prognostic factor for mortality among elderly hip fracture patients. The burden of minor cognitive dysfunction is likely superimposed on that of delirium in subgroups of frail patients.